Gerromorpha y Nepomorpha (Heteroptera) del Pacífico de Colombia: lista de especies, distribución geográfica y altitudinal (2016)
The bibliographical information about the species of aquatic Heteroptera, infraorders Gerromorpha and Nepomorpha, from the Colombian Pacific Plain was compiled. A total of 106 species are included, grouped in 14 families and 39 genera. Additionally, for each species the geographic distribution by region and department, and the altitudinal range are presented.